Notifikasi Real-time Pada Sistem Nurse Call Nirkabel Berbasis Zigbee Menggunakan Protokol WebSocket - Billy Montolalu; Hamzah Ulinuha Mustakim; Nilla Rachmaningrum (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2021)
Nurse Call System, a system used by inpatients to call nurses if they need help. This system is very useful for patients with disabilities such as being unable to speak, unable to walk, and no family in the form of a telephone or a button attached to a wall. The weakness of the system with permanent position is mobility, for example when the patient is going to the bathroom and unwanted things happen, the patient will have difficulty asking for help. So, a wireless Nurse Call system is needed that can be carried wherever the patient goes so that the patient can call the nurse wherever needed. In this research, nurse call system was developed wirelessly via the ZigBee data communication and realtime notification using websocket protocol. The development stages were carried out: literature study and field observation, development of Zigbee push buttons and gateways, development of middleware to read data from gateways, development of dashboard and reporting application. The last stage of monitoring and evaluation is testing the system that has been made. Based on the test results performed the system can run well when the distance between the zigbee push button and the gateway is less than 15 meters and has a response time of less than 1634 milliseconds.